Dairy Attenuates Weight Gain to a Similar Extent as Exercise in Rats Fed a High‐Fat, High‐Sugar Diet. Issue 10 (7th August 2017) - Trottier, Sarah K.; MacPherson, Rebecca E.K.; Knuth, Carly M.; Townsend, Logan K.; Peppler, Willem T.; Mikhaeil, John S.; Leveille, Cameron F.; LeBlanc, Paul J.; Shearer, Jane; Reimer, Raylene A.; Wright, David C.
Abstract : Objective: To compare the individual and combined effects of dairy and endurance exercise training in reducing weight gain and adiposity in a rodent model of diet‐induced obesity. Methods: An 8‐week feeding intervention of a high‐fat, high‐sugar diet was used to induce obesity in male Sprague‐Dawley rats. Rats were then assigned to one of four groups for 6 weeks: (1) casein sedentary (casein‐S), (2) casein exercise (casein‐E), (3) dairy sedentary (dairy‐S), and (4) dairy exercise (dairy‐E). Rats were exercise trained by treadmill running 5 d/wk. Results: Dairy‐E prevented weight gain to a greater extent than either dairy or exercise alone. Adipose tissue and liver mass were reduced to a similar extent in dairy‐S, casein‐E, and dairy‐E groups. Differences in weight gain were not explained by food intake or total energy expenditure. The total amount of lipid excreted was greater in the dairy‐S compared to casein‐S and dairy‐E groups. Conclusions: This study provides evidence that dairy limits weight gain to a similar extent as exercise training and the combined effects are greater than either intervention alone. While exercise training reduces weight gain through increases in energy expenditure, dairy appears to increase lipid excretion in the feces.